Biomimetic microstructural reorganization during suture retention strength evaluation of electrospun vascular scaffolds. Issue 8 (10th August 2015) - Chaparro, Francisco J.; Matusicky, Michelle E.; Allen, Matthew J.; Lannutti, John J.
Abstract: Suture retention strength (SRS) is commonly used as a measure the ability of sutures to adhere implants to surrounding tissue. While SRS is widely employed, surprisingly its effects on graft microstructure have not been characterized. This is particularly germane to the broad utilization of electrospun implants in tissue engineering. These implants need to retain their initial nanoscale topography while simultaneously preserving clinically critical mechanical properties. We examined the suture‐driven microstructural deformation of polycaprolactone electrospun to form both square and tubular SRS samples. The impact of fiber orientation (generally parallel or random orientation, orthogonally aligned) on the SRS of these vascular tissue equivalents was analyzed and compared to native and decellularized porcine vasculature. The initial state of the fiber clearly dictates the overall efficiency of scaffold utilization. SRS values for as‐spun fibers at a thickness of 300 μm were found to be in the range of 1.59–4.78 N for the three orientations. Unexpectedly, random fibers provided the optimal SRS values based on both resistance to suture motion and the percentage of scaffold involvement. A "V‐shaped" failure morphology is observed for both electrospun scaffolds and native tissue during SRS testing. Post‐test fiber alignment in the tensile direction was visible in all initial fiber orientations similar to that of native tissue. These findings are significant as they allow us to employ new, counterintuitive biomimetic design criteria for nanofiber‐based scaffolds in which reliable mechanical integration with the surrounding tissues via suture‐based methods is important. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1525–1534, 2016.